Double-resistance anti-corrosion powder coating

By combining self-healing coatings and phase change material coatings in the powder coating, the problem of powder coatings being difficult to last for a long time in harsh environments in the prior art is solved, and the risk of static electricity accumulation is reduced through automatic repair and high temperature thermal protection, achieving longer service life and higher safety.

CN119799095APending Publication Date: 2025-04-11FUJIAN WANAN IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510049442.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing dual-resistant anti-corrosion powder coatings are difficult to protect the pipe surface for a long time in harsh environments, and the accumulation of coal dust may lead to the accumulation of static electricity, increasing the risk of electrostatic discharge.

Method used

Using a combination of self-healing coatings and phase change material coatings, self-healing coatings include acrylic resins, carbon black, polyurethane particles and silica, and phase change material coatings contain polypropylene, corrosion-resistant additives, phase change polymers, talc and silica, and through specific formulations and processes, a powder coating that can automatically repair and provide additional thermal protection in high temperature environments.

Benefits of technology

Self-healing coatings can be quickly repaired when minor damage is encountered, extending the life of the coating and reducing maintenance costs. Phase change material coatings provide additional thermal protection in high temperature environments, reducing the risk of static accumulation and improving overall safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799095A_ABST
    Figure CN119799095A_ABST
Patent Text Reader

Abstract

The invention discloses a double-anti-corrosion powder coating, and relates to the technical field of coatings. Comprising a powder coating composed of 60-75 wt% of acrylic resin, 10-20 wt% of carbon black, 5-15 wt% of polyurethane particles and 5-10 wt% of silicon dioxide. The phase-change material coating comprises a powder coating consisting of 55 to 60 weight percent of polypropylene, 20 to 30 weight percent of an anti-corrosion additive, 10 to 14 weight percent of a phase-change polymer, 2 to 5 weight percent of talcum powder and 1 to 3 weight percent of silicon dioxide. Through the arrangement of the self-repairing coating and the phase-change material coating, in the using process, the self-repairing coating can be automatically repaired when being slightly damaged, the service life of the coating is prolonged, the maintenance cost is reduced, the repairing process is rapid, and the service life of the coating is prolonged. The completeness of the coating can be recovered in a short time, a continuous protection effect is provided, static accumulation can be effectively reduced, and potential risks caused by electrostatic discharge are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a double-resistance and anti-corrosion powder coating. Background Art

[0002] Double anti-corrosion powder coating is mainly used on pipes used underground in coal mines to improve the corrosion resistance, wear resistance and weather resistance of the pipes, extend the service life of the pipes and reduce maintenance costs. This coating is usually made by applying a special polyethylene plastic powder or epoxy resin powder material on the inner and outer surfaces of the steel pipe through a special process. It has anti-static, flame retardant and anti-corrosion properties, overcoming the defects of the steel pipe itself, such as easy rust, corrosion, high pollution, and the low strength and easy deformation of the plastic pipe.

[0003] For example, the patent publication number is CN101503593A, which is based on domestic epoxy powder E 12 and phenolic modified epoxy, dicyandiamide and sebacic acid dihydrazide as curing agents, polyvinyl butyral and ultra-high molecular weight polyethylene as toughening and leveling, and silicon carbide, cast stone powder and graphite as anti-wear and self-lubricating support. Through energy-saving manufacturing process and hot melt coating, a unique anti-wear and corrosion-resistant powder coating is formed. It is a heavy anti-corrosion powder with outstanding anti-wear properties. It can be used to strengthen the inner wall surface anti-wear function of oil field pumping well oil pipes caused by eccentric wear of pumping rods, and is extended to metal parts with enhanced anti-wear function in corrosive environments.

[0004] However, during the use of the above-mentioned powder, due to the setting of its internal powder coating, the powder coating is exposed to acid and alkali corrosion, mechanical wear and high temperature in harsh environments for a long time, and the protective effect of the coating is difficult to last. At the same time, the coal dust in coal mines is a good insulator. The accumulation of coal dust may lead to the generation of static electricity. Over time, the accumulation of coal dust on the surface of the pipe will increase the risk of static electricity accumulation. In order to solve this problem, a double-anti-corrosion powder coating was invented to meet the use needs. Summary of the invention

[0005] The object of the present invention is to provide a dual-anti-corrosion powder coating to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions: a dual-anticorrosion powder coating, comprising a self-repairing coating and a phase change material coating; The self-repairing coating comprises a powder coating consisting of 60-75wt% acrylic resin, 10-20wt% carbon black, 5-15wt% polyurethane particles and 5-10wt% silicon dioxide; The phase change material coating comprises a powder coating consisting of 55-60wt% polypropylene, 20-30wt% anti-corrosion additives, 10-14wt% phase change polymer, 2-5wt% talc and 1-3wt% silicon dioxide.

[0007] Furthermore, the steps for making the self-healing coating and the phase change material coating are as follows: S1: Raw material preparation, selecting polymer as the base material, determining epoxy resin as the repair agent particles, and determining the phase change polymer and its phase change temperature range; S2: Raw material preparation, washing the raw materials, removing impurities and unnecessary components, and grinding them; S3: coating preparation: putting the pretreated raw materials into a batching container, adding the self-healing coating and the phase change material coating for preparation; S4: coating mixing, adding the processed ingredients and additives into the mixing container according to the formula ratio, and fully mixing and evenly dispersing the coating mixture and calcium carbonate through a stirring device; S5: filtering and removing impurities, filtering the reacted coating to remove solid particles, impurities and sediments to obtain pure coating; S6: Drying treatment, drying the filtered paint to remove excess water in the paint, and sieving the dried powder paint to adjust the particle size to obtain paint powder.

[0008] Furthermore, in the step S2, the raw material is ground to control the diameter of the particles within 10 μm.

[0009] Furthermore, the anti-corrosion additive is an additive with zinc powder or aluminum powder as raw materials.

[0010] Furthermore, the process of preparing the coating consists of the following steps: Step 1: Material preparation: prepare the required raw materials, including acrylic resin, modifier, polyurethane particles, polyurethane particles, silica, talc, polypropylene, phase change polymer and silica, and check the solid content of the resin; Step 2: Weighing and mixing: Weigh the required raw materials according to a certain ratio, and then put the raw materials into the batching container for mixing and stirring; Step 3: Coating: Spray and dip the mixed phase change powder coating and self-repairing powder coating onto the substrate and conduct testing; Step 4: Viscosity adjustment: Change the rheological properties of the coating by adding talc and silica; Step 5: Formula optimization and testing: Test and evaluate the coating, test the corrosion resistance and oxidation resistance of the coating, and optimize and adjust the coating formula.

[0011] Furthermore, the stirring time in step S4 is 5-30 minutes.

[0012] Furthermore, in the step S4, the coating mixture and the calcium carbonate are stirred in a mixing ratio of (1.5-2.5):1.

[0013] Furthermore, the calcium carbonate needs to be ground during the dissolution process.

[0014] Compared with the prior art, the present invention has the following beneficial effects: This dual anti-corrosion powder coating is provided with a self-repairing coating and a phase change material coating. During use, the self-repairing coating can automatically repair itself when slightly damaged, thereby extending the service life of the coating and reducing maintenance costs. The repair process is fast and the integrity of the coating can be restored in a short time, providing a continuous protective effect. It can effectively reduce the accumulation of static electricity and reduce the potential dangers caused by static electricity discharge. It is highly practical and suitable for promotion.

[0015] At the same time, when the coating is used in high temperature and flammable environments, it can improve the overall safety of the substrate. The specific resins and additives contained in the formula can effectively resist corrosive media such as acids, alkalis, and salts, and protect the substrate from external damage. The optimized formula can significantly improve the durability of the coating and is suitable for use in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The present invention is a schematic flow chart of a method for preparing a dual-anti-corrosion powder coating. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] The present invention provides a technical solution: a dual-anti-corrosion powder coating, which has broad application potential in multiple fields and provides reliable protection for various surfaces. It also has certain advantages in terms of aesthetics and decoration. In order to demonstrate the technical solution in detail, 6 embodiments are provided for verification.

[0019] Each of the following embodiments adopts a dual-anti-corrosion powder coating provided by the present technical solution, including a self-repairing coating and a phase change material coating; including a self-repairing coating and a phase change material coating; The self-healing coating comprises a powder coating composed of 60-75wt% acrylic resin, 10-20wt% carbon black, 5-15wt% polyurethane particles and 5-10wt% silica; the phase change material coating comprises a powder coating composed of 55-60wt% polypropylene, 20-30wt% anti-corrosion additives, 10-14wt% phase change polymers, 2-5wt% talc and 1-3wt% silica, and the anti-corrosion additive is an additive with zinc powder or aluminum powder as raw materials.

[0020] The steps for making self-healing coating and phase change material coating are as follows: S1: Raw material preparation, selecting polymer as the base material, determining epoxy resin as the repair agent particles, and determining the phase change polymer and its phase change temperature range; S2: Raw material preparation, washing the raw materials, removing impurities and unnecessary components, and grinding the raw materials to control the particle diameter within 10 μm; S3: coating preparation: putting the pretreated raw materials into a batching container, adding the self-healing coating and the phase change material coating for preparation; S4: coating mixing, adding the processed ingredients and additives into a mixing container according to the formula ratio, and fully mixing and evenly dispersing the coating mixture and calcium carbonate through a stirring device; the stirring time is 5-30 minutes, and the coating mixture and calcium carbonate are stirred in a mixing ratio of (1.5-2.5):1 in step S4, and the calcium carbonate needs to be ground during the dissolution process; S5: filtering and removing impurities, filtering the reacted coating to remove solid particles, impurities and sediments to obtain pure coating; S6: Drying treatment, drying the filtered paint to remove excess water in the paint, and sieving the dried powder paint to adjust the particle size to obtain paint powder.

[0021] The coating preparation process consists of the following steps: Step 1: Material preparation: prepare the required raw materials, including acrylic resin, modifier, polyurethane particles, polyurethane particles, silica, talc, polypropylene, phase change polymer and silica, and check the solid content of the resin; Step 2: Weighing and mixing: Weigh the required raw materials according to a certain ratio, and then put the raw materials into the batching container for mixing and stirring; Step 3: Coating: Spray and dip the mixed phase change powder coating and self-repairing powder coating onto the substrate and conduct testing; Step 4: Viscosity adjustment: Change the rheological properties of the coating by adding talc and silica; Step 5: Formula optimization and testing: Test and evaluate the coating, test the corrosion resistance and oxidation resistance of the coating, and optimize and adjust the coating formula.

[0022] It should be noted that the self-repairing coating and the phase change material coating are configured in a ratio of 1.5:1 for the implementation of Examples 1 to 3, and the self-repairing coating and the phase change material coating are configured in a ratio of 2.5:1 for the implementation of Examples 4 to 6; Example 1: The self-healing coating prepared by coating formulation comprises 600 g (60 wt%) of acrylic resin, 200 g (20 wt%) of carbon black, 150 g (15 wt%) of polyurethane particles and 50 g (5 wt%) of silicon dioxide; The formulated phase change material coating of the coating comprises 550 g (55 wt %) of polypropylene, 300 g (28) wt % of anti-corrosion additive, 140 g (14 wt %) of phase change polymer, 20 g (2 wt %) of talc and 10 g (1 wt %) of silica.

[0023] Example 2: The self-healing coating prepared by coating formulation comprises 650 g (65 wt %) of acrylic resin, 150 g (15 wt %) of carbon black, 100 g (10 wt %) of polyurethane particles and 100 g (10 wt %) of silicon dioxide; The formulated phase change material coating of the coating comprises 560 g (56 wt %) of polypropylene, 250 g (25 wt %) of anti-corrosion additive, 120 g (12 wt %) of phase change polymer, 50 g (5 wt %) of talc and 20 g (2 wt %) of silica.

[0024] Example 3: The self-healing coating prepared by coating formulation comprises 750 g (75 wt %) of acrylic resin, 130 g (13 wt %) of carbon black, 50 g (5 wt %) of polyurethane particles and 70 g (7 wt %) of silicon dioxide; The formulated phase change material coating of the coating comprises 600 g (60 wt%) of polypropylene, 220 g (22 wt%) of anti-corrosion additive, 100 g (10 wt%) of phase change polymer, 50 g (5 wt%) of talc and 30 g (3 wt%) of silica.

[0025] Example 4: The self-healing coating prepared by coating formulation comprises 750 g (75 wt %) of acrylic resin, 130 g (13 wt %) of carbon black, 50 g (5 wt %) of polyurethane particles and 70 g (7 wt %) of silicon dioxide; The formulated phase change material coating of the coating comprises 600 g (60 wt%) of polypropylene, 220 g (22 wt%) of anti-corrosion additive, 100 g (10 wt%) of phase change polymer, 50 g (5 wt%) of talc and 30 g (3 wt%) of silica.

[0026] Example 5: The self-healing coating prepared by coating formulation comprises 650 g (65 wt %) of acrylic resin, 150 g (15 wt %) of carbon black, 100 g (10 wt %) of polyurethane particles and 100 g (10 wt %) of silicon dioxide; The formulated phase change material coating of the coating comprises 560 g (56 wt %) of polypropylene, 250 g (25 wt %) of anti-corrosion additive, 120 g (12 wt %) of phase change polymer, 50 g (5 wt %) of talc and 20 g (2 wt %) of silica.

[0027] Example 6: The self-healing coating prepared by coating formulation comprises 600 g (60 wt%) of acrylic resin, 200 g (20 wt%) of carbon black, 150 g (15 wt%) of polyurethane particles and 50 g (5 wt%) of silicon dioxide; The formulated phase change material coating of the coating comprises 550 g (55 wt %) of polypropylene, 300 g (28) wt % of anti-corrosion additive, 140 g (14 wt %) of phase change polymer, 20 g (2 wt %) of talc and 10 g (1 wt %) of silica.

[0028] Comparative Example 1: Using commercially available graphene zinc-rich anti-corrosion coating.

[0029] Verification test: The corrosion resistance is verified by the following tests: drying test and weathering test; The oxidation resistance is verified by the following tests: salt spray test and acid immersion test; Drying test: For the drying test, first determine the temperature and humidity of the test environment. The temperature is set between 20°C and 25°C, and the humidity is set between 40% and 60%. Apply the coating sample evenly on the substrate. After the coating is completed, start timing immediately, record the start time, and continue to observe the changes in the coating sample. When the coating is completely dry, stop timing and record the drying time. Take the average of the 3 test results to obtain the following data and make the data into the following table; Weather resistance test: The four levels of weather resistance evaluation are: Level 0, Level 1, Level 2, and Level 3, where Level 0 represents the highest weather resistance. The weather resistance test consists of the following steps: Step 1: High temperature: The surface temperature of the coating sample is controlled at 70°C, and the air temperature needs to be controlled between 40% and 60%; Step 2: Watering cycle; control the water temperature at 15℃; Step 3: heating-freezing cycle, heating raises the sample surface temperature to 50℃, and freezing the sample surface temperature to -20℃.

[0030] Observe and record the specimens after each high temperature, water spray cycle and each heating-cooling cycle, take the average of the three test results, and obtain the following data and make the data into the following table; Salt spray test: Set the test conditions of the salt spray test equipment such as temperature, humidity and salt spray concentration, start the salt spray test equipment, generate mist containing salt, regularly observe the corrosion of the coating samples, record the changes, corrosion degree and time, take the average of the three test results, obtain the following data and make the data into the following table; Electrostatic test: The electrostatic discharge method was used to conduct the experiment, and the average value of the test results was taken for 3 times to obtain the following data and the data was made into the following table;

[0031] Through the comparative data, it can be concluded that the dual anti-corrosion powder coating, through the setting of self-healing coating and phase change material coating, during use, the self-healing coating can automatically repair itself when it is slightly damaged, thereby extending the service life of the coating and reducing maintenance costs. The repair process is fast and can restore the integrity of the coating in a short time, providing continuous protection. The phase change material can absorb or release heat within a specific temperature range, which helps to regulate the temperature of the substrate surface, improve heat resistance, and provide additional thermal protection. It is suitable for high temperature environments to prevent thermal damage and material degradation.

[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is limited by the attached embodiments and their equivalents.

Claims

1. A dual-anti-corrosion powder coating, characterized in that: Its formula is: Including self-healing coatings and phase change material coatings; The self-repairing coating comprises a powder coating consisting of 60-75wt% acrylic resin, 10-20wt% carbon black, 5-15wt% polyurethane particles and 5-10wt% silicon dioxide; The phase change material coating comprises a powder coating consisting of 55-60wt% polypropylene, 20-30wt% anti-corrosion additives, 10-14wt% phase change polymer, 2-5wt% talc and 1-3wt% silicon dioxide.

2. A dual-anticorrosion powder coating according to claim 1, characterized in that: The steps for making the self-healing coating and the phase change material coating are as follows: S1: Raw material preparation, selecting polymer as the base material, determining epoxy resin as the repair agent particles, and determining the phase change polymer and its phase change temperature range; S2: Raw material preparation, washing the raw materials, removing impurities and unnecessary components, and grinding them; S3: coating preparation: putting the pretreated raw materials into a batching container, adding the self-healing coating and the phase change material coating for preparation; S4: coating mixing, adding the processed ingredients and additives into the mixing container according to the formula ratio, and fully mixing and evenly dispersing the coating mixture and calcium carbonate through a stirring device; S5: filtering and removing impurities, filtering the reacted coating to remove solid particles, impurities and sediments to obtain pure coating; S6: Drying treatment, drying the filtered paint to remove excess water in the paint, and sieving the dried powder paint to adjust the particle size to obtain paint powder.

3. A dual-anticorrosion powder coating according to claim 2, characterized in that: In the step S2, the raw material is ground to control the diameter of the particles within 10 μm.

4. The dual-anticorrosion powder coating according to claim 1, characterized in that: The anti-corrosion additive is an additive with zinc powder or aluminum powder as raw materials.

5. The dual-anticorrosion powder coating according to claim 2, characterized in that: The process of coating preparation consists of the following steps: Step 1: Material preparation: prepare the required raw materials, including acrylic resin, modifier, polyurethane particles, polyurethane particles, silica, talc, polypropylene, phase change polymer and silica, and check the solid content of the resin; Step 2: Weighing and mixing: Weigh the required raw materials according to a certain ratio, and then put the raw materials into the batching container for mixing and stirring; Step 3: Coating: Spray and dip the mixed phase change powder coating and self-repairing powder coating onto the substrate and conduct testing; Step 4: Viscosity adjustment: Change the rheological properties of the coating by adding talc and silica; Step 5: Formula optimization and testing: Test and evaluate the coating, test the corrosion resistance and oxidation resistance of the coating, and optimize and adjust the coating formula.

6. The dual-anticorrosion powder coating according to claim 2, characterized in that: The stirring time in step S4 is 5-30 minutes.

7. The dual-anticorrosion powder coating according to claim 2, characterized in that: In the step S4, the coating mixture and the calcium carbonate are stirred in a mixing ratio of (1.5-2.5):

1.

8. The dual-anticorrosion powder coating according to claim 1, characterized in that: The calcium carbonate needs to be ground during the dissolution process.

Citation Information

Patent Citations

  • Anti-corrosive anti-abrasion coating powder for metal pipeline

    CN101503593A